2006
DOI: 10.1073/pnas.0509639103
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for histone N-terminal recognition by human peptidylarginine deiminase 4

Abstract: Histone arginine methylation is a posttranslational modification linked to the regulation of gene transcription. Unlike other posttranslational modifications, methylation has generally been regarded as stable, and enzymes that demethylate histone arginine residues have not been identified. However, it has recently been shown that human peptidylarginine deiminase 4 (PAD4), a Ca 2؉ -dependent enzyme previously known to convert arginine residues to citrulline in histones, can also convert monomethylated arginine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
131
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(137 citation statements)
references
References 33 publications
5
131
1
Order By: Relevance
“…Although the molecular mechanism of how PADI4 increases DNA accessibility was not fully elucidated, loss of positive charge by citrullination was shown to induce conformational changes of histone H4 N terminal 40 . DNA-histone interaction is chargedependent, and changes in the charge of the histone tails are considered to weaken histone-DNA interaction 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the molecular mechanism of how PADI4 increases DNA accessibility was not fully elucidated, loss of positive charge by citrullination was shown to induce conformational changes of histone H4 N terminal 40 . DNA-histone interaction is chargedependent, and changes in the charge of the histone tails are considered to weaken histone-DNA interaction 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Given the phenotypic switch in shPAD4 cells, we sought to identify putative targets of PAD4 that might account for induction of the EMT phenotype. Crystallographic data suggest that PAD4 does not recognize specific arginine residues in a unique sequence context but rather recognizes five successive residues with the consensus sequence 1 ϕXRXX 5 , in which ϕ denotes amino acids with small side-chain moieties, and X denotes any amino acid (21). The target sequence must also be accessible and flexible enough to fit into the active pocket of PAD4, much like the N-terminal sequence SGRGK of human histones H4 and H2A, whose arginine at position 3 (R3) is one of the better described targets of PAD4 (14,21,22).…”
Section: Stable Knockdown Of Pad4 Induces Emt and Increases The Invasivementioning
confidence: 99%
“…Crystallographic data suggest that PAD4 does not recognize specific arginine residues in a unique sequence context but rather recognizes five successive residues with the consensus sequence 1 ϕXRXX 5 , in which ϕ denotes amino acids with small side-chain moieties, and X denotes any amino acid (21). The target sequence must also be accessible and flexible enough to fit into the active pocket of PAD4, much like the N-terminal sequence SGRGK of human histones H4 and H2A, whose arginine at position 3 (R3) is one of the better described targets of PAD4 (14,21,22). Because initiating methionines (M) often are removed during protein maturation, we searched the proteome for sequences beginning with an amino (N)-terminal MSGR motif using pBLAST and PredMod (23).…”
Section: Stable Knockdown Of Pad4 Induces Emt and Increases The Invasivementioning
confidence: 99%
“…A recent study with PAD2, PAD3, and PAD4 enzymes found that PAD4 prefers histone H3, whereas PAD2 prefers actin for citrullination (11). However, the interaction of PAD4 with its substrate peptides is mainly mediated by the peptide backbone (58), suggesting that PAD4 may target Arg residues embedded in a diverse range of substrates. To date, histones H3, H4, and H2A, ING4, nucleophosmin, and nuclear lamin C have been identified as substrate of PAD4.…”
Section: Discussionmentioning
confidence: 99%